(untitled) (Comillas Journal of International Relations, 2020)
The popularization of the Internet provides great space for freedom of expression and association, resulting in the increase on access to information by citizens. Furthermore, it is often claimed that there is a causal relationship between the emergence of the Internet and the empowerment of the civil society as well as the advent of democracy. However, this cyberutopia is frequently challenged by a wide range of states. Facing the conservative dilemma, coined by George Schultz, these governments respond to it by producing propaganda and by establishing control mechanisms instead of shutting down the Internet. In this regard, the main objective of this paper has consisted in shedding light on how the Venezuelan government is employing the Internet to control dissident movements within their national borders. Extensive research, with a special focus on Twitter, has proved that Chavism has benefitted from the Internet to expand its control on the Net.